Taxable Income vs. Financial Income: How Much Uniformity Can We Stand? - Arnett, Harold E. (The Accounting Review, 1969)
Debate on the question of correlation between taxable income and financial income has run "hot and heavy" for many years. Most individual accountants writing on this question argue that greater harmony, if not complete agreement, should exist between the two. The American Accounting Association (AAA) and the American Institute of Certified Public Accountants (AICPA) did not take official positions on the issue until some two decades ago. At that time, however, they agreed with the majority view. Most of these individuals and organizations emphasized that taxation principles should be brought more closely in harmony with generally accepted accounting principles, rather than the reverse. The method of accomplishing this objective was also dearly indicated. Instead of incorporating accounting principles and applications into statutes to make "book income" and "taxable income" identical products of legislative fiat, their recommendations have stressed that accounting concepts incorporated into statutes defining taxable income should be based on parallel accounting principles developed in the market place. In a word, accountants feel they should influence congressional action on tax matters, but that governmental agencies should not prescribe generally accepted accounting principles. The purpose of this writing has not been to convince the reader that all of the objectives sought by accountants with regard to taxation provisions are wrong. Rather, the object has been to convince the reader that in their present official posture the AICPA and the AAA are not Ekely to reach these objectives without serious consequences to the profession.